The Influence of Mcdonald's Application on Consumer Satisfaction and Purchasing Decisions among Students in Bandung City - Zaydan, Fathi (Asosiasi Ahli Administrasi Indonesia, 2024)
This research aims to explore the impact of the McDonald's application on satisfaction and purchasing decisions among Bandung City students. The application is considered a symbol of the company's adaptation to technological advances and digitalization in the modern era. The research method applied was descriptive-quantitative, with data collection using questionnaires, involving 109 Bandung City students as respondents. The research results concluded that the McDonald's application had a significant role in influencing student satisfaction and purchasing decisions. The application of technology through applications creates a satisfying experience for consumers, having a positive impact on purchasing decisions. These findings highlight the need for companies to adapt to technological developments to meet consumer expectations, especially among digitally active students. In conclusion, the McDonald's application plays a positive role in creating satisfaction and influencing student purchasing decisions in Bandung City.